Generic redefinition, key and two new species of Acorystus Townes (Hymenoptera: Ichneumonidae: Cryptinae) - Scherrer, Marcus V.; Santos, Bernardo F.; Aguiar, Alexandre P. (Zootaxa, 2010)
The taxonomic limits of Acorystus are reviewed. The genus is characterized by a body surface shiny and mostly impunctate, supra-antennal area with a conical horn, epomia and posterior transverse carina of propodeum entirely absent, ovipositor tip very slender, without nodus and with very weak teeth. Two new taxa, A. albicornis Scherrer et Santos, sp. nov., and A.circumflexus Scherrer et Santos, sp. nov., are described and illustrated. Acorystus albicornis is diagnosed mainly by the white band of the female flagellum covering only about five flagellomeres, supra-antennal area with a white central horn, with a very weak and slightly rugose longitudinal swelling, orbital band reaching supra-clypeal and supra-antennal areas, propodeum with anterior transverse carina almost straight, and pleural carina very weak, with short transverse wrinkles. It is recorded from two close localities at Espírito Santo State (19º57’55”S 40º32’25”W and 20º16’21”S 40º28’40”W), in the Atlantic Forest of Southeastern Brazil. Acorystus circumflexus is diagnosed mainly by the white band of the female flagellum covering about fifteen flagellomeres, supra-antennal area with a black central horn, with a strong and rugose longitudinal swelling, orbital band absent, propodeum with anterior transverse carina centrally arched forwards, and pleural carina entirely absent. It is recorded only from Caxiuanã (2º4’54”S 51º51’5”), Eastern Amazon Basin. A key to all three known species of the genus is provided.